Association between abdominal obesity and depressive symptoms in Peruvian women aged 18-49 years: A sub-analysis of the Demographic and Family Health Survey 2018-2019 - Leon-Zamora, Sharon (2024)
Objective: Abdominal obesity (AO) is characterised by excess adipose tissue. It is a metabolic risk that affects the physical and mental health, particularly in women since they are more prone to mental health problems like depression. This study investigated the association between AO and depressive symptoms in Peruvian women of reproductive age (18-49 years). Design: This is a cross-sectional observational study. Setting: Peruvian women population of reproductive age. Participants: We used data from the Peruvian Demographic and Family Health Survey (DHS) for 2018 and 2019 to assess 17 067 women for the presence of depressive symptoms (using the Patient Health Questionnaire (PHQ-9): cut-off score ≥ 10) and AO (measured by abdominal circumference; cut-off score ≥88 cm). Results: We observed a 64·55 % prevalence of AO and 7·61 % of depressive symptoms in the study sample. Furthermore, 8·23 % of women with AO had depressive symptoms (P < 0·05). Initially, women with AO appeared to have a 26 % higher risk of depressive symptoms compared with women without AO (P = 0·028); however, after adjustment for covariates, no statistically significant association was observed. Conclusions: Therefore, although both conditions are common in women of this age group, no significant association was found between AO and depressive symptoms.